Rugosidad superficial de resinas nanohíbridas bajo la acción de tres sistemas de pulido. Universidad Nacional de Chimborazo 2018 - Altamirano Sánchez, Anthony Efraín (2018)
After the era of discovering the composite resin by L. Bowen in 1962, odontology evolved significantly in order to provide teeth a natural appearance. It was a fundamental point for aesthetic success; however, restoration durability depended on a polished finish. It gave to the composite a similar surface to the dental enamek. The objective of this research work was to identify yhe average surface roughness(Ra) of the nanohybrid resin under the action of three disk polishing systems. Twenty disc samples of 10mm diameter with 0.2 mm thickness of nanohybrid resin were made. They were divided into four groups, including the contraol group, each group was subjected to a polishing system (disks) of different selling stores. To measure the average surface roughness of the resin, a profilometer was used. The study compared the groups. The control group showed a very significant difference in mean roughness; meanwhile, the disc polishing system caused less roughness. It was Super-Sanp from FGM. Sof-LexTM disk from the commercial house 3M-ESPE, its polishing system, caused more roughness.